Analisis Kontrastif Adjektiva Amai dalam Bahasa Jepang dan Adjektiva Manis dalam Bahasa Indonesia - Saputri, Suryani Yayuk; Sutedi, Dedi; Rasiban, Linna Meilia (Vocational College of Diponegoro University, 2025)
This study discusses the contrastive analysis of the adjective amai in Japanese and the adjective manis in Indonesian. This study aims to identify and analyze the similarities and differences between amai adjective in Japanese and manis adjective in Indonesian in terms of the study of semantics (meaning). The method used is contrastivemesra analysis method. To see the similarities and differences between the adjectives amai and manis, a pairing technique that refers to linguistic linguistic phenomena by Koyanagi (2004) is used. The data in this study used jitsurei from the corpus shonagon.ninjal.ac.jp, nlb.ninjal.ac.jp and online newspapers asahi.com, yahoo.ac.jp, tribunnews.com, and detik.com. The results of this study found 4 similarities and 8 differences between the adjectives amai and manis. The meaning similarities are about sweetness, fragrant, melodious, and friendly. Furthermore, the differences in meaning include intimate, naive, loose, seducing, pampering, beautiful, polite, and beautiful. In addition, this study found linguistic phenomena is the icchi, shinki, and ketsujo phenomena. This study only uses data sources from corpus and online newspapers, so further research is recommended to use more varied data sources such as magazines, literary works in the form of novels, and other sources to find more similarities and differences in the meaning of the two adjectives.